Between Global Competition and National Justice: The Legal Protection Dilemma in Indonesia - T. Keizerina Devi Azwar; Utary Maharany Barus (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
This article examines Indonesia’s legal-protection dilemma amid intensifying global competition. Addressing a gap in prior literature that treats globalization’s legal effects descriptively, we evaluate the effectiveness of Indonesia’s legal protection through the lenses of legal certainty (Radbruch), distributive justice (Rawls), and institutional quality (North). Using a normative juridical method—statute, conceptual, and comparative approaches—our analysis of WTO-related disputes and domestic regulatory practice shows: First, persistent disharmony and overlap across trade, investment, and IPR regimes; Second, weak and uneven enforcement that erodes legal certainty; and Third, structural asymmetries in international fora impacting national justice goals. We propose targeted reforms: accelerated regulatory harmonization aligned with international commitments, capacity-building for trade-remedy and IPR enforcement, and calibrated safeguards for MSMEs within ASEAN and WTO frameworks. These steps reconcile competitiveness with national justice, strengthening Indonesia’s legal readiness in a globalized economy.